Implementasi Etika Bisnis dan Kualitas Produk Pada Novel Rendez-Vous Di Angkringan Paijan Karya Kimberly Harjawinata - Retika Sari, Olivia; Narayanti, Luh; Kurniawan, Eva Dwi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Angkringan is a place for appointments for all groups. The angkringan owner, who heard all the conversations in his tent, ended up becoming a victim of fighting. Not only are they victims of fighting against each other, angkringan owners are faced with the problem of increasing prices for production materials. These two things cause angkringan traders to be able to maintain their business. This research uses a qualitative method with descriptive results and also uses a heuristic reading method, namely by reading thoroughly. The data source was taken from the novel